1982
DOI: 10.1007/bf00046830
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic variation in cancer metastasis: immune escape versus immune control

Abstract: Antigenic variation in cancer metastasis was observed in a syngeneic murine tumor system consisting of a low metastatic parental tumor line (derived from a methylcholanthrene-induced DBA/2 T lymphoma, Eb), a high metastatic spontaneous variant thereof (ESb), and a low metastatic 'revertant' from ESb (ESb-M). All three lines expressed tumor-associated transplantation antigens (TATA) which elicited specific T cell-mediated antitumor immune reactions in the host. The strongest host response was elicited upon intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 91 publications
(102 reference statements)
3
47
0
Order By: Relevance
“…The murine bend3 endothelioma cell line was kindly provided by Dr. W. Risau (Bad Nauheim, FRG) and was maintained in DMEM with high glucose (Life Technologies, Eggenstein, FRG) containing 10% low endotoxin fetal bovine serum (FBS) (Life Technologies). Cells were activated with LPS from Salmonella enteritidis (Sigma, Deisenhofen, FRG) at a dose of 1 #g/ml for 4 h at 37~ The T cell lymphoma line TK-1 (13,27), the lymphoma cell lines ESb 289 and Eb (28), and the B lymphoma line L1-2 were maintained in RPMI 1640 medium supplemented with 10% FBS, 2 mM L-glutamine, 10 mM Hepes, and 50 mM 2-ME (culture medium). The T cell hybridoma cell line BI 141 (29) was kindly provided by A. Reske-Kunz (University of Mainz, Mainz, FRG) and was maintained in Iscove's medium supplemented with 5% FBS, sodium pyruvate, and 50 mM 2-ME.…”
Section: Methodsmentioning
confidence: 99%
“…The murine bend3 endothelioma cell line was kindly provided by Dr. W. Risau (Bad Nauheim, FRG) and was maintained in DMEM with high glucose (Life Technologies, Eggenstein, FRG) containing 10% low endotoxin fetal bovine serum (FBS) (Life Technologies). Cells were activated with LPS from Salmonella enteritidis (Sigma, Deisenhofen, FRG) at a dose of 1 #g/ml for 4 h at 37~ The T cell lymphoma line TK-1 (13,27), the lymphoma cell lines ESb 289 and Eb (28), and the B lymphoma line L1-2 were maintained in RPMI 1640 medium supplemented with 10% FBS, 2 mM L-glutamine, 10 mM Hepes, and 50 mM 2-ME (culture medium). The T cell hybridoma cell line BI 141 (29) was kindly provided by A. Reske-Kunz (University of Mainz, Mainz, FRG) and was maintained in Iscove's medium supplemented with 5% FBS, sodium pyruvate, and 50 mM 2-ME.…”
Section: Methodsmentioning
confidence: 99%
“…This surprising in vivo finding raised the question as to whether ESb-M cells were still ESb-type cells. We therefore examined ESb-M cells for the expression of cell-surface markers that can discriminate between Eb and ESb type cells (4,5,7). ESb-M cells were found to be Thy-l-, Lyt-1 +, Lyt-2-, Fc receptor-positive and possessed the ESbtype tumor antigen (TATAEsb) ( Table I) thus showing a similar phenotype as ESb cells.…”
Section: Methodsmentioning
confidence: 99%
“…It is easily accessible without the need for pre-treatments such as shaving, and has been demonstrated to be a privileged organ for the induction of protective antitumor immune responses. 19,20,26 An interesting point is the detection of ␤-gal expressing cells in the draining lymph node after i.e. injection of lacZ.…”
Section: -Induced Immune Responses To Different Lacz Plasmid Expressimentioning
confidence: 99%
“…In previous studies with the ESb tumor system it was shown that the ear pinna is a privileged site for the induction of antitumor immunity, 19 preventing the outgrowth of an otherwise lethal dose of tumor cells. Thus it was reasonable to test the ear pinna also as a putative site for DNA vaccination and to compare the strength of the immune response to that induced by ␤-gal expressing tumor cells.…”
Section: Introductionmentioning
confidence: 99%